Numerical Experiments with the Fokker–Planck Equation in 1D Slab Geometry. Issue 3 (15th April 2016) - Pouso, Óscar López; Jumaniyazov, Nizomjon
ABSTRACT: Several numerical experiments with the steady monoenergetic Fokker–Planck equation in the one-dimensional (1D) slab are performed and discussed. Planar-geometry symmetry is assumed. Results are obtained with a new numerical scheme of order 2 based on finite differences.